Acute cocaine administration alters permeability of blood-brain barrier in freely-moving rats— Evidence using miniaturized fluorescence microscopy. (1st January 2020) - Barr, Jeffrey L.; Brailoiu, G. Cristina; Abood, Mary E.; Rawls, Scott M.; Unterwald, Ellen M.; Brailoiu, Eugen
Highlights: The effect of cocaine on BBB was examined using miniscope implanted in adult rats. Cocaine transiently increased Na fluorescein extravasation in brain microvessels. In awake rats cocaine increased BBB permeability in dose-and time-dependent manner. Abstract: Background: Cocaine has a variety of negative effects on the central nervous system, including reports of decreased barrier function of brain microvascular endothelial cells. However, few studies have directly shown the effects of cocaine on blood-brain barrier (BBB) function in vivo . The miniature integrated fluorescence microscope (i.e., miniscope) technology was used to visualize cocaine-induced changes in BBB permeability in awake, freely-moving rats. Methods: The miniscope was implanted in the prefrontal cortex of adult male rats. After recovery and acclimation, rats received an injection of cocaine (5-20 mg/kg ip) 15 minutes following iv infusion of sodium fluorescein, a low molecular weight tracer. Fluorescence intensity was recorded in vivo via the miniscope for 30 minutes or 24 hours post cocaine administration and served as an indicator of BBB permeability. Results: Results demonstrate that cocaine increased the sodium fluorescein extravasation in brain microcirculation in a dose-dependent manner 30 minutes, but not 24 hours after administration. Conclusion: We report for the first time using direct visualization of brain microcirculation with the miniscope technology in awake, freely-moving rats, that acute cocaine administration produced a transient increase in the BBB permeability.